The Role Of Parent In Increasing Student English Learning Achievement In SMP Negeri I Weru - Choiriyah, Isnaeni, Drs. Djoko Srijono, M.Hum, Dra. Dwi Haryanti, M.Hum (2013)
The research paper aims at finding the parent's role in improving their children's English learning achievement, describing the factors affecting the parent in improving their children's English learning achievement, and finding the obstacles the parent faces in improving their children's English learning achievement. In this study, the writer employs a descriptive qualitative research which describes the role of parent in increasing student English learning achievement on SMP Negeri I WERU. Subject of research is the VIIE grader consisting of 34 students of SMP Negeri 1 Weru. The object of research is the role of parents and learning achievement. The methods of collecting data are interview and document. The results of the research show that, firstly, the role of parents in improving their children's English learning achievement, they are: (a) Parents provide child emotional support; (b) Parents provide child instrumental support, and (c) Parents provide guidance on child in for those having English competency. Second, factors affecting parents in improving their children's English learning achievement: (a) the poor English learning achievement of the students; majority (70%) students attain less than 6 score in English; (b) parents consider English as an important subject, and (c) parents desire to make their children attaining better score for English subject than they attain in the present. Finally, the constraints of the parents face in improving their children's English learning achievement, they are: (a) parents inability of speaking English; (b) low learning motivation of to student, and (c) the parents could fulfill their children needs, because of the economic condition.